Road Freight in Central America : Five Explanations to High Costs of Service Provision - World Bank (World Bank, Washington, DC, 2017)
An efficient system to transport goods domestically and internationally is a key element of the logistics chain. Road freight transport has a direct impact on poverty as it employs millions of people and generates a significant portion of Gross Domestic Product, or GDP, especially in low and middle-income countries. Trucking is the primary form of transportation for domestic, trans-border, and international cargo, in Central America. Road freight transport is now vital to production, distribution, and mobilization, driving economic, social, and environmental progress. In short, trucking is the backbone of economies around the world. In the past 20 years, the industry has advanced as technology has improved communication, management, productivity, including vehicle efficiency. Their objective in doing so is to expand markets, generate wealth on the basis of efficient specialization, introduce competition, and lower costs for production, distribution, services, and research and development. When road freight transport services are efficient, they support these objectives; when they are not they act as nontariff barriers to trade, creating delays, raising costs, worsening congestion and pollution. Such barriers prolong and destabilize delivery schedules, hinder 'just in time' inventory management and industrial processes, and impede the efficient combination of factors of production.